Perimortem Cesarean Section : As Resucitative Hysterotomy On Maternal Cardiac Arrest - Madona Utami Dewi; Syahredi Syaiful Adnani; Emilzon Taslim (Andalas Obstetrics And Gynecology Journal, 2020)
Maternal cardiac arrest or maternal collaps is defined as an acute event involving the cardiorespiratory systems and/or brain, resulting in a reduced or absent consciousness level (and potentially death), at any stage in pregnancy and up to six weeks after delivery. Perimortem Cesarean Section (PCS) is performed either during maternal cardiac arrest or during impending maternal cardiac arrest toresuscitate mother and fetal. Current recommendations for maternal resuscitation include performance of the procedure following five minutes of unsuccessful cardiopulmonary resuscitation. The most common aetiology of maternal collaps was know as “4 H and  4 T” (Hypovolemia, Hypoxia, Hypo/Hyperkalemia,Hypothermia; Tromboembolism, Toxicity, Tension pneumothorax, Tamponade). Resuscitation in maternal cardiac arrest is mostly similar with non-pregnant patient resuscitation. There are several considerations need to be addressed in primary survey such as endotracheal tube 1 size smaller, supplemental O2 regardless of peripheral saturation, aggressive volume resuscitation, and uterine displacement to relieve compression of the IVC.Keywords: Maternal cardiac arrest; non-pregnant patient resuscitation